Republic of Tunisia : Strategy for Public Debt Management - World Bank (Washington, DC, 2013)
The need for an effective public debt management strategy has increased with Tunisia's stronger presence in the international financial markets and the larger exposure to changing borrowing conditions and exchange rate fluctuations. At the same time, there are better conditions today for public debt management, with the deepening the secondary market for Tunisian debt instruments on the international bond market, while the public debt management strategy would be greatly strengthened by the steps taken to develop the domestic government securities market. This study discusses options to the reform of the government public debt management practices, with the aim of increasing their efficiency, consolidating further the country's market access and containing the costs and risks of borrowing in both external and domestic markets. The study is intended to facilitate the introduction of an action plan for the implementation of the public debt management strategy, as part of the set of measures aiming at strengthening the macroeconomic framework in Third Economic Competitiveness Adjustment Loan Project (report no. P7489). Chapter One presents debt sustainability scenarios and discusses the underlying vulnerability factors. Chapter Two examines key principles of a strategy for public debt management, and presents a discussion of how active risk management can be progressively introduced in Tunisia. The analysis benchmarks Tunisia's debt situation against other emerging economies with comparable characteristics. Chapter Three addresses reform options to step up the development of domestic government securities market-a key component of the strategy. Finally, Chapter Four considers options in institutional reforms that would facilitate the implementation of the desired innovations in debt management strategy and operations.